Analisis Peran Teknologi Pendidikan Dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Kristen - Norianti Pai Tiba; Noviarni Taneo; Nofrianti Enliyani Tualaka; Trilin Ndoen; Rani Yuniati Naek; Priska. A Leo; Yentro Kurnyatu Djo; Elkana Manimalai; Fernando Tualaka (Indo Publishing, 2026)
This study analyzes the role of educational technology in enhancing the quality of Christian Religious Education (CRE) learning. The aim of the research is to explore the utilization of educational technology in CRE and its impact on student motivation. The method employed is a literature review with data collection from various sources. The results indicate that the use of technology-based learning media, such as interactive videos and digital platforms, enhances student interactivity and participation. Furthermore, educational technology contributes to increasing student motivation and facilitates more flexible learning. However, challenges related to teachers' competence in integrating technology and maintaining a balance between technological and spiritual aspects still need attention. These findings demonstrate that educational technology can serve as an effective means in supporting quality CRE learning that is relevant to the needs of the 21st century and aligned with Christian faith values.